Development of a core outcome set for cardiovascular diabetology: a methodological framework - Jiao, Jiao; Chen, Lingmin; Peng, Yong; Jia, Qingyi; He, Ying; Zhang, Yonggang; Li, Nian (Frontiers in Endocrinology, 2023)
Background: Cardiovascular diabetology is an emergent field focusing on all aspects of diabetes/cardiovascular interrelationship and metabolic syndrome. High-quality evidence needs to be provided to determine the efficacy and safety of interventions in Cardiovascular diabetology. Heterogeneity of outcomes among trials limits the comparison of results, and some outcomes are not always meaningful to end-users. The cardiovascular diabetology core outcome set (COS) study aims to develop a COS of interventions for cardiovascular diabetology. In this paper, we introduce the methodological framework for developing the COS. Methods: The COS development will include the following steps: a) establish the COS groups of stakeholders, including international steering committee, Delphi survey group and consensus meeting group; b) systematic reviews of outcomes used in trials of cardiovascular diabetology; c) semi-structured interview of stakeholders for outcomes of cardiovascular diabetology; d) generate a list of candidate outcomes and determine the original outcome pool; e) Delphi survey with stakeholders of cardiovascular diabetology to select potential core outcomes; f) review and endorse the cardiovascular diabetology COS by expert consensus meeting. Conclusions: This current study reports the methodological framework to develop a COS in cardiovascular diabetology and will provide evidence for future development of COS in cardiovascular diabetology.